Hubungan Tingkat Kecemasan Ibu Terhadap Pemberian ASI - Monica, Lisa (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Abstract Introduction: Postpartum mothers go through several stages, namely taking in, where the mother is worried about her body and is not used to caring for her baby, resulting in anxiety for the mother, then the taking hold stage where the mother is unable to be responsible for caring for her child, and the final stage is letting go where Mother has taken over the responsibility to take good care of her baby. Objective: to determine the relationship between the anxiety level of postpartum mothers and breastfeeding. Methods: This study uses a correlation descriptive design with a cross sectional approach. Respondents in this study used a purposive sampling technique, namely as many as 85 respondents. Research Results: After conducting research on the relationship between postpartum maternal anxiety and breastfeeding, the majority (58.5%) of the normal age category (20-35 years), Muslim (59.3%) some mothers have babies aged 15-19 weeks (21.2%), primiparous (43.2%), normal type of delivery (52.5%), the majority of mothers with high school education (44.1%), most mothers work as housewives (56.8%), the last type of delivery was the majority normal (66.1%). The majority of anxiety levels for postpartum mothers are at a moderate level (47.5%) and as many as (27.1%) mothers breastfeed their babies. Based on the results of statistical tests, it can be concluded that there is a relationship between postpartum maternal anxiety and breastfeeding in the working area of the Payung Sekaki Health Center (p value = 0.018). Conclusion: There is a relationship between maternal anxiety and breastfeeding at the Payung Sekaki Health Center.